Symptom heterogeneity and patient subgroup classification among US patients with post-treatment Lyme disease: an observational study - Ting Yang; Alison W Rebman; John N Aucott (BMJ Open, 2021)
Objectives To identify underlying subgroups with distinct symptom profiles, and to characterise and compare these subgroups across a range of demographic, clinical and psychosocial factors, within a heterogeneous group of patients with well-defined post-treatment Lyme disease (PTLD).Design A clinical case series of patents.Setting Participants were recruited from a single-site, Lyme disease referral clinic patient population and were evaluated by physical exam, clinical laboratory testing and standardised questionnaires.Participants Two hundred and twelve participants met study criteria for PTLD, with medical record-confirmed prior Lyme disease as well as current symptoms and functional impact.Results Exploratory factor analysis classified 30 self-reported symptoms into 6 factors: ‘Fatigue Cognitive’, ‘Ocular Disequilibrium’, ‘Infection-Type’, ‘Mood-Related’, ‘Musculoskeletal Pain’ and ‘Neurologic’. A final latent profile analysis was conducted using ‘Fatigue Cognitive’, ‘Musculoskeletal Pain’ and ‘Mood-Related’ factor-based scores, which produced three emergent symptom profiles, and participants were classified into corresponding subgroups with 59.0%, 18.9% and 22.2% of the sample, respectively. Compared with the other two groups, subgroup 1 had similarly low levels across all factors relative to the sample as a whole, and reported lower rates of disability (1.6% vs 10.0%, 12.8%; q=0.126, 0.035) and higher self-efficacy (median: 7.5 vs 6.0, 5.3; q=0.068,<0.001). Subgroup 2 had the highest ‘Musculoskeletal Pain’ factor-based scores (q≤0.001). Subgroup 3 was characterised overall by higher symptom factor-based scores, and reported higher depression (q≤0.001).Conclusions This analysis identified six symptom factors and three potentially clinically relevant subgroups among patients with well-characterised PTLD. We found that these subgroups were differentiated not only by symptom phenotype, but also by a range of other factors. This may serve as an initial step towards engaging with the symptom heterogeneity that has long been observed among patients with this condition.